Pengaruh Faktor Fundamental Terhadap Harga Saham Sektor Industri Real Estate di Bursa Efek Indonesia (BEI) - Agatha Tumanggor; Audrey Audrey; Christine Simatupang; Dewi Lowisa; Diah Ayu; Dimas Arza; Enjelina Samosir; Immanuel Siahaan; Ishak Munawar; Kasih Simbolon; Nova Sitinjak; Rifka Sibuea; Rini Sartika (Konstanta : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2024)
The Indonesian capital market is experiencing significant growth, encouraging investors to consider shares as the main investment option. Fundamental analysis is important in assessing company performance, especially in the property and real estate sectors which are important for the Indonesian economy. This research aims to analyze the influence of fundamental factors such as Return On Assets (ROA), Return On Equity (ROE), Debt to Equity Ratio (DER), and Book Value (BV) on the share prices of property and real estate companies listed on the Indonesia Stock Exchange (BEI) for the 2021-2023 period. Using a panel data regression model with a random effects approach, the results show that BV has a partially significant positive effect on stock prices, while ROA, ROE and DER have a partially significant negative effect. These findings provide insight for investors in identifying key factors that influence share prices, so that they can help in making better investment decisions in the property and real estate sector.